EFFECTIVENESS OF HYDROTHERAPY ON IMPROVING FUNCTIONAL ABILITY IN CASES OF LOW BACK MECHANICAL PAIN AT PERDAGANGAN REGIONAL HOSPITAL - Isaharpika Br Ginting; Yeni Trisna Purba; Sontoso Simanjuntak (Mount Hope Economic Global Journal, 2025)
Low Back Pain is one of the symptoms that is often described with pain that occurs in the lumbar or lumbosacral area which attacks 7.3% in 540 million people in 2015. The most common LBP is mechanical LBP with the cause of Hernia Nucleus Pulposus and nonspecific (idiopathic). This condition causes functional and movement disorders so that the patient requires physiotherapy intervention, one of which is hydrotherapy. The research method in writing this article is a literature review through four databases, namely Science Direct, EBSCOhost, Google Scholar, and PubMed on March 26, 2021, in according to the PICO framework and inclusion criteria. The measuring tools that can be used to assess functional ability are ODI, MODI, QBPDS, and RMDQ. Effectiveness of hydrotherapy to improve functional ability in mechanical LBP cases. There is an increase in functional ability in mechanical LBP during the 8-week training period with a training dose of 3 sessions/week, 8-10 repetitions and 60 minutes/session time and the Recommended methods are walking, ROM exercise, stretching exercise, strengthening exercise, squats, lunges., stabilization exercises, US well US pedaling and cycling. The administration of hydrotherapy is effective in increasing functional ability in mechanical LBP patients with various parameters and taking into account various things, such US dosage and exercise methods.